2012
DOI: 10.3892/ol.2012.815
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive effect of regulatory T lymphocytes in lung cancer, with special reference to their effects on the induction of autologous tumor-specific cytotoxic T lymphocytes

Abstract: Abstract. It is not easy to induce cytotoxic T lymphocytes (CTLs) against cancer in in vitro culture. Regulatory T cells (Tregs) are considered to play a pivotal role in tumor immune escape. In this study, we analyzed the distribution of Tregs among tumor-infiltrating lymphocytes (TILs), regional lymph node lymphocytes (RLNLs) and peripheral blood lymphocytes (PBLs) in patients with lung cancer, and analyzed the effect of Tregs on the induction of CTLs in vitro.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 41 publications
0
16
0
1
Order By: Relevance
“…Some studies have shown that during the early stage of differentiation, Treg cells may require TGF-β, which is secreted by TAMs, to hamper immunoregulatory responses (15). Other studies have demonstrated that Treg cells may mediate immunosuppression by IL-10 in the tumor microenvironment (25)(26)(27). With respect to Treg cells, Islas-Vazquez et al proposed that IL-10 may participate in the differentiation process of Treg cells in lung adenocarcinoma (28).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that during the early stage of differentiation, Treg cells may require TGF-β, which is secreted by TAMs, to hamper immunoregulatory responses (15). Other studies have demonstrated that Treg cells may mediate immunosuppression by IL-10 in the tumor microenvironment (25)(26)(27). With respect to Treg cells, Islas-Vazquez et al proposed that IL-10 may participate in the differentiation process of Treg cells in lung adenocarcinoma (28).…”
Section: Discussionmentioning
confidence: 99%
“…+ Treg cells, as a minor yet important group of T cells, mediate immune suppression and immune incompetency, and play a role in negative immune regulation and maintain the stability of the internal environment of an organism through contacts between cells and cytokine secretion (Shigematsu et al, 2012). CD127, as the alphachain receptor of IL-7, has been shown to play an important role in the proliferation, differentiation, and maturation of T cells.…”
Section: Discussionmentioning
confidence: 99%
“…Tregs are thought to be a major cause of tumor-driven immune evasion, which is a major obstacle to the development of effective immunotherapies. Our previous studies demonstrated that the Tregs in the regional lymph nodes of NSCLC patients inhibited the induction of cytotoxic T lymphocytes (CTLs) against autologous tumor cells, and the depletion of Tregs restored the induction of CTLs [18]. Foxp3 has been used as hallmark of Tregs, because it is a master regulator for the differentiation and function of Tregs [19].…”
Section: Discussionmentioning
confidence: 99%